Global prediction of recessions - Dovern, Jonas; Huber, Florian (Economics letters, 2015)
We present evidence that global vectorautoregressive (GVAR) models produce more accurate recession forecasts than country-specific time-series models in a Bayesian framework. This result holds for most countries and forecast horizons as well as for several country groups.
Gesehen am 25.06.2020